Materia Medica of New and Old Homeopathic Medicines - Riley, David S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Materia Medica of New and Old Homeopathic Medicines David S. Riley$1 (Bs interest in the research and subsequently the history and methodology of homeopathic drug provings began with his medical school training in 1979 and a residency in Internal Medicine. He was exposed to homeopathy in 1988 followed by study at the Hahnemann College of Homeopathy in Albany, California. He has investigated the interplay between contemporary research methods and the research methods associated with homeopathic drug provings. Dr Riley has developed research tools for data collection, symptom selection criteria and blinding; primarily to address the risk of bias. The homeopathic drug provings published here are the result of this work. For the 3rd edition twelve homeopathic drug provings, conducted by a number of internationally renowned proving directors, have been added. These homeopathic drug provings all follow good clinical practice (GCP) research guidelines and incorporate the guidelines suggested by Dr Samuel Hahnemann more than 200 years ago.s
Homeopathic drug provings -- Acidum alpha-ketoglutaricum -- Acidum alpha-lipoicum -- Acidum ascorbicum -- Acidum cis-aconiticum -- Acidum citricum -- Acidum fumaricum -- Acidum malicum -- Acidum oroticum -- Acidum succinicum -- Adenosinum monohydrogen phosphoricum (cAMP) -- Adenosinum triphosphoricum (ATP) -- Agnus castus -- Anthrachinonum -- Arteria suis -- Ascophyllum nodosum -- Bacterium coli -- Baryta oxalsuccinicum -- Benzochinonum, para -- Bryonia alba -- Bryonia dioica -- Calendula officinalis -- Cardiospermum halicacabum -- Cartilago suis -- Caulophyllum thalictroides -- Cerebrum suis -- Coenzymum A -- Colocynthis -- Cuprum formicicum -- Cyanocobalaminum -- Cysteinum -- Discus intervertebralis suis -- Embryo suis -- Fucus vesiculosus -- Fumaria officinalis -- Funiculus umbilicalis suis -- Galphimia glauca -- Geranium robertianum -- Glandula suprarenalis suis -- Glyoxalum -- Hepar suis -- Hydrochinonum -- Hypophysis suis -- Hypothalamus suis -- Kalium tetraiodobismutatum -- Levothyroxinum -- Luffa operculata -- Magnesium gluconicum -- Magnesium oroticum -- Mahonia aquifolium -- Manganum phosphoricum -- Medulla ossis suis -- Methylglyoxalum -- Mucosa nasalis suis -- Mucosa suis -- Myosotis arvensis -- Nadidum -- Naphthochinonum -- Natrium oxalaceticum -- Natrium pyruvicum -- Nicotinamidum -- Okoubaka aubrevillei -- Oleander -- Oleum pini -- Oxalis acetosella -- Pancreas suis -- Pelargonium sidoides -- Placenta suis -- Pyridoxinum hydrochloricum -- Riboflavinum -- Sinusitisinum -- Staphylococcus nosode -- Streptococcus nosode -- Symphytum officinale -- Terebinthina laricina -- Thiaminum hydrochloricum -- Tormentilla -- Trichinoylum -- Tuba uterina suis -- Ubichinonum -- Urtica urens -- Uterus suis -- Vena suis -- Veronica officinalis -- Zincum aceticum -- Zincum gluconicum -- Appendix .
Keywords: Alternative medicine; Complementary and Alternative Medicine; Materia Medica; Formulary, Homeopathic